26. Rhythmic activity of leg muscles during standing in healthy subjects. Issue 4 (April 2016) - Marinelli, L.; Massaro, W.N.; Romaggi, D.; Leandri, S.; Leandri, M.
Abstract : Traditionally, the stretch and possibly polysynaptic reflexes are considered the mainstay of antigravity leg muscles. We found evidence of a different mechanism. In a group of young normal subjects, surface EMG was recorded from tibialis anterior, soleus, vastus medialis and biceps femoris muscles in quiet upright stance without and with balance perturbation. In quiet stance, a modest amount of activity could be recorded from the soleus and the biceps femoris only, and none from tibialis anterior and vastus medialis. Such activity was organized in bursts whose duration ranged 50–100 ms, and frequency of 8–12/s. Simultaneous recording of the centre of pressure via stabilometric platform, showed that when a forward shift occurred, frequency and amplitude of the soleus bursts increased, but all activity ceased in a backward shift. When balance was perturbed by a backward tilt, the very first ensuing activity was a brief response by the soleus (weak stretch reflex) followed by several bursts of the tibialis anterior. Little if any activity was recorded from the thigh muscles. We conclude that action of antigravity muscles of the leg seemed more linked to modulation of a rhythmic preordinated activity rather than to a simple reflex response.